Dual Antifungal and Immunoregulatory Actions of Topical Silver Nanoparticles from Piper ornatum Extract in Cutaneous Candida albicans Infection - Dewi, Firli Rahmah Primula; `Mustofa, Laila Al Azizi; Hamdin, Candra Dwipayana; Geraldi, Almando; Lim, Vuanghao; Pramudya, Manikya; Hayati, Alfiah; Hajar, Versa Rachmania (Pandawa Institute, 2026)
Cutaneous Candida albicans infection is characterized by persistent inflammation, epidermal damage, and dysregulated immune responses. Silver nanoparticles (AgNPs) have emerged as promising antifungal agents with additional immunomodulatory properties; however, their effects on skin pathology and local immune responses during candidiasis remain incompletely defined. This study aimed to investigate the therapeutic effects of a topical AgNP-based cream in a murine model of C. albicans–induced skin infection. AgNPs were green-synthesized using an aqueous leaf extract of Piper ornatum. A murine model of cutaneous C. albicans infection was established, and infected mice were treated topically with AgNP-based cream formulations at concentrations of 4% or 6%. Disease severity was assessed through macroscopic skin evaluation and histopathological analysis. Immune modulation was examined by flow cytometric analysis of CD4⁺ T-cell subsets expressing TNFα and IL-17, as well as CD11b⁺ myeloid cells expressing IL-6 and IL-10. Untreated infected mice exhibited severe cutaneous pathology, including persistent erythema, erosive lesions, epidermal hyperkeratosis, and acanthosis. These changes were accompanied by marked immune dysregulation, characterized by expansion of CD4⁺IL-17⁺ T-cells, suppression of TNFα-producing CD4⁺ T-cells, increased IL-6 expression, and reduced IL-10 production in CD11b⁺ myeloid cells. Topical AgNP treatment significantly ameliorated macroscopic and histological skin damage, restoring epidermal architecture toward normal. Immunologically, AgNP therapy attenuated pathological Th17 responses, reduced IL-6-producing myeloid cells, enhanced IL-10 expression, and maintained TNFα at controlled levels. Both AgNP concentrations were effective, with the 4% AgNP formulation showing slightly superior normalization of epidermal thickness and inflammatory markers. Overall, topical AgNP-based cream effectively alleviated cutaneous C. albicans infection by combining antifungal activity with coordinated immunomodulation of both adaptive and innate immune responses. By suppressing excessive IL-17– and IL-6–driven inflammation while promoting regulatory immune pathways, AgNP treatment supports tissue repair and immune homeostasis, highlighting its potential as a therapeutic strategy for cutaneous candidiasis.